Peculiarities of ex vitro growing completion of bog cranberry (Vaccinium oxycoccos L.) with a closed root system - I. V. Nechiporenko; S. V. Akimova; P. O. Kazakov (Овощи России, 2023)
Timeliness. The prerequisites for the cultivation of bog cranberry (Vaccinium oxycoccos L.) in industrial plantations have led to an increased demand for high quality planting material obtained by clonal micropropagation (in vitro). Studies have been carried out on the of ex vitro growing completion of cranberry plants using different mineral fertilizers and types of light under greenhouse conditions.Methods. Ex vitro plants of a selected form of cranberry (Vaccinium oxycoccos L.) obtained using the clonal micropropagation technique were the objects of research. Experimental adapted cranberry plants were planted in 0.5 L containers in 'Veltorf' peat substrate with an acidity of at least pH 3.5-4.0, to which mineral fertilizers were added according to the variants: APAVIVA N15P15K15(S10) 0.08 and 0.16 g/L, Sulfoammophos N16P20(S12) 0.072 and 0.144 g/L, N12P52 0.1 and 0.2 g/L, control without fertilizer. The plants were placed under different types of light: under LED phytolamps (UnionPowerStar – 40W-T) with a photoperiod of 16 hours and under natural light (without the use of additional lighting) under greenhouse conditions.Results. It was found that during of the ex vitro growing completion of bog cranberry (Vaccinium oxycoccos L.) plants in containers, the advantage of LED phytolamps was revealed, when using them in all experimental variants on the 42nd day of growing the morphometric indicators of plant development were almost 2 times higher than in plants grown under natural light. The type of mineral fertilizers and type light significantly influenced the total length of shoots (82.9±13.74- 107.4±35.95 cm vs. 58.6±20.92 cm in control) and leaf surface area (41.1±6.46-54.1±4.67 cm2 vs. 22.9±9.63 cm2 ). Conclusion. The results we obtained contributed to a better representation of the ex vitro growing conditions of bog cranberry (Vaccinium oxycoccos L.) plants using different types of lighting (phyto-lighting with a 16-hour photoperiod and natural light – without adding additional light) and the selection of optimal doses of mineral nutrition. The best, under LED lighting, were N16P20(S12) at a concentration of 0.072 g/L and N15P15K15(S10) at a concentration of 0.16 g/L.